Patient-reported outcomes for the Intergroup Sentinel Mamma study (INSEMA): a randomised trial with persistent impact of axillary surgery on arm and breast symptoms in patients with early breast cancer - Reimer, Toralf; Stachs, Angrit; Veselinovic, Kristina; Polata, Silke; Müller, Thomas; Kühn, Thorsten; Heil, Jörg; Ataseven, Beyhan; Reitsamer, Roland; Hildebrandt, Guido; Knauer, Michael; Golatta, Michael; et al. (EClinicalMedicine, 2023)
Background In clinically node-negative breast cancer patients, the INSEMA trial (NCT02466737) assessed the noninferiority of avoiding sentinel lymph node biopsy (SLNB) or axillary lymph node dissection (ALND). Here we present patient-reported outcomes (PROs) as a secondary endpoint.
Available online 25 November 2022
Gesehen am 13.03.2023